Peran Guru Kreatif dalam Membentuk Karakter Siswa di Era Revolusi Industri - Mukaromah, Nisaul; Ningsih, Tutuk (At-Tadris: Journal of Islamic Education, 2024)
This article discusses the role of creative teachers in shaping student character in the era of the Industrial Revolution 4.0, especially in the context of Islamic education. The focus of this research is the importance of integration between technology and character education to create students who are smart, noble, and able to adapt to global changes. This research uses a library research method with a descriptive-analytical qualitative approach. This study found that the role of teachers in character education is very important, especially in the era of the Industrial Revolution 4.0. Creative teachers who utilize technology can integrate Islamic character values effectively. The use of social media and digital platforms as learning tools is also proven to support students' character building, creating relevant and impactful learning.The conclusion of this study emphasizes the importance of teachers' roles as role models and facilitators in character education, especially in the era of the Industrial Revolution 4.0. Islamic education should utilize technology effectively while maintaining religious values. Curriculum development and teaching methods.